Patient perspectives on quality of care for depression and anxiety in primary health care teams: A qualitative study - Rachelle Ashcroft; Matthew Menear; Andrea Greenblatt; Jose Silveira; Simone Dahrouge; Nadiya Sunderji; Monica Emode; Jocelyn Booton; Marvelous Muchenje; Rachel Cooper; Asante Haughton; Kwame McKenzie (Wiley, 2021)
Abstract Background Widespread policy reforms in Canada, the United States and elsewhere over the last two decades strengthened team models of primary care by bringing together family physicians and nurse practitioners with a range of mental health and other interdisciplinary providers. Understanding how patients with depression and anxiety experience newer team‐based models of care delivery is essential to explore whether the intended impact of these reforms is achieved, identify gaps that remain and provide direction on strengthening the quality of mental health care. Objective The main study objective was to understand patients' perspectives on the quality of care that they received for anxiety and depression in primary care teams. Methods This was a qualitative study, informed by constructivist grounded theory. We conducted focus groups and individual interviews with primary care patients about their experiences with mental health care. Focus groups and individual interviews were recorded and transcribed verbatim. Grounded theory guided an inductive analysis of the data. Results Forty patients participated in the study: 31 participated in one of four focus groups, and nine completed an individual interview. Participants in our study described their experiences with mental health care across four themes: accessibility, technical care, trusting relationships and meeting diverse needs. Conclusion Greater attention by policymakers is needed to strengthen integrated collaborative practices in primary care so that patients have similar access to mental health services across different primary care practices, and smoother continuity of care across sectors. The research team is comprised of individuals with lived experience of mental health who have participated in all aspects of the research process.